INDIAN ORGANIC AGRICULTURE: THE CURRENT SITUATION (International Journal of Food and Nutritional Sciences, 2022)
India has emerged as one of the top three countries in the world where the area under organic agriculture expanded the maximum in 2020, according to latest data.Natural farming is not a new concept in India, with farmers having tilled their land without the use of chemicals - largely relying on organic residues, cow dung, composts, etc. since time immemorial.Food quality and safety are the primary concerns of Indian consumers today. The growing environmental and food safety concerns have created a significant demand for yield from green and sustainable cultivation methods. Modern farming methods often lead to biodiversity loss and monoculture, which are huge factors in the environment’s decline. Pesticides and chemical usage are rampant in Indian agriculture, causing water and soil contamination.